(untitled) (Economic and Political Thought, 2020)
The aim of the article is to present the dynamics of the formation of social cooperatives and their possibilities in the socioeconomic sphere. Social cooperatives are a type of social economy entities in Poland. At the same time, they constitute an entity closest to and most often classified as a social enterprise due to its social mission as well as a part of the profit allocated for this purpose. The Polish state still has difficulties in introducing social market economy and social transfers are not able to solve all the problems because this concept works only when it is not treated randomly and is applied in accordance with the rules, i.e. coherently, in the long term and above all in the categories of the economic order. As a result, as well as in the face of socioeconomic problems that the epidemic will generate, the authors of the study see a social cooperative as a social enterprise that is an entity helping the state to deal with such problems as unemployment, homelessness or disability.